Pengaruh Disiplin Belajar Terhadap Hasil Belajar Siswa Kelas XI SMA Negeri 8 Kota Jambi - Aprilia, Anita; Kasiono, Kasiono (Universitas Batanghari Jambi, 2025)
This study aims to determine the effect of learning discipline on the learning outcomes of class XI students in economics subjects at SMA Negeri 8 Jambi City. The research method used in this study is a quantitative method using simple linear regression analysis techniques. The research subjects were students of SMA Negeri 8 Jambi City with a sample of 195 students using simple random sampling. The results of the study showed that the acquisition of the coefficient value B constant = 1.498 stated that if the variable of learning discipline was ignored, then the learning outcomes = 0.009 with a value of t count X = 90.488, so the hypothesis stating that there was a significant influence between learning discipline on the learning outcomes of class XI students in economics subjects at SMA Negeri 8 Jambi City in this study was accepted.